Kemampuan Laba Kotor, Laba Operasi, Laba Bersih dan Perubahaan Piutang dalam Memprediksi Arus Kas Operasi di Perusahaan Manufaktur - Riyanti .; Sultan .; Zikra Supri; Sahrir .; Sofyan Syamsuddin (Jurnal Ekonomika dan Bisnis, 2022)
This study aims to determine which concepts are best in predicting cash flow operating activities and provide empirical evidence regarding gross profit, operating profit, net income and changes in accounts receivable in predicting cash flows for operating activities in the future by testing each variable. The object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2015. The results of this study indicate that changes in accounts receivable have the best ability compared to gross profit, operating profit and net income in predicting future operating cash flows. Partially only the change of accounts receivable variable that proved to significantly affect the dependent variable (operating cash flow).